2008
DOI: 10.1093/glycob/cwn132
|View full text |Cite
|
Sign up to set email alerts
|

Homolog of the maize  -glucosidase aggregating factor from sorghum is a jacalin-related GalNAc-specific lectin but lacks protein aggregating activity

Abstract: Recently, we identified the maize beta-glucosidase aggregating factor (BGAF) as a jacalin-related lectin (JRL) and showed that its lectin domain is responsible for beta-glucosidase aggregation. By searching for BGAF homologs in sorghum, we identified and obtained an EST clone and determined its complete sequence. The predicted protein had the same modular structure as maize BGAF, shared 67% sequence identity with it, and revealed the presence of two potential carbohydrate-binding sites (GG...ATYLQ, site I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The above results clearly indicate that the deletion of dirigent domain in SL also alters the sugar specificity of its JRL domain. We have shown that SL is a monomer but with two sugar-binding sites [2]. Our gel-filtration data suggest that its JRL domain is also monomeric.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…The above results clearly indicate that the deletion of dirigent domain in SL also alters the sugar specificity of its JRL domain. We have shown that SL is a monomer but with two sugar-binding sites [2]. Our gel-filtration data suggest that its JRL domain is also monomeric.…”
Section: Resultsmentioning
confidence: 57%
“…and they are distinct [1]. SL on the other hand, exhibits exclusive specificity for GalNAc, but it does not participate in proteineprotein interactions [2]. In this report, we show that deletion of the dirigent domain in BGAF and SL affects the sugar specificity of their lectin domains, indicating that the dirigent domains play a role in influencing the carbohydrate-binding specificity in this class of modular lectins.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations